The grouping and matching of three dimensional deviation based on homogeneous transformation and Taguchi theory - Wei SUN; Xiaokai MU; Qingchao SUN; Yingjie JIANG (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2017)
The precision of mechanical equipment closely associated with parts manufacturing precision. This article mainly to realize the machine precision on the basis of low manufacturing accuracy of parts through the homogeneous coordinate transformation and the Taguchi theory. Firstly, using the homogeneous coordinate transformation to establish the transfer accumulation model of machine precision. Secondly, the mathematical model of three dimensional tolerance based on the new generation Geometrical Product Specification (GPS) is built. Thirdly, this paper establishes the tolerance matching model based on Taguchi method and Taguchi orthogonal table model to improve the machine assembly precision without increasing manufacturing cost. Finally, with the example of horizontal machining center to discuss the 3D deviation transmission accumulation model, through the comparison analysis between the random combination method and the Taguchi orthogonal table on controlling the accumulated deviation show that the control effect of the first group’s experimental scheme for Taguchi orthogonal table is worst, while the third group is best. In a word, building the best deviation combination scheme of statistical significance not only reduce the cost, but also improve the overall assembly quality and has a certain guiding significance for the actual production.